EFEKTIVITAS SENAM YOGA TERHADAP PENINGKATAN KEMAMPUAN KOGNITIF LANSIA: THE EFFECTIVENESS OF YOGA EXERCISE ON INCREASING COGNITIVE ABILITY IN THE ELDERLY - Yestiani Norita Joni; Safitri, Safitri (STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2020)
Entering old age, self-awareness is needed to maintain health status in order to avoid illness or health problems. One disease that often occurs in the elderly is a disorder of cognitive change. Cognitive disorders in the elderly are usually called dementia (senility), if the elderly experience symptoms such as disturbances such as attention (attention), memory, (memory), place and time orientation, construction and execution capabilities (such as making decisions, solving problems) signs of awareness it has occurred or without any disturbance of consciousness. At present, the management of cognitive change is nonpharmacology. One of the nonpharmacological procedures is doing yoga exercises for the elderly. Doing yoga exercises is one of the therapies that can improve cognitive functioning, and stress so that cognitive functions experience relaxation making an increase in cognitive change in the elderly. This study aims to determine the effect of yoga gymnastics on cognitive change in the elderly at the Social Institution of Tresna Werdha Budi Mulia 4 Cengkareng, West Jakarta. This type of quantitative research uses non-probability samples one-group pre-post test design without control. The sampling technique is using a total sampling technique of 20 respondents. The intervention is as much as 3 days. Analysis of the data used is univariate and bivariate analysis with wilcoxon. This study shows that there is a p value = 0,000 <p = 0.05. Which means that there is an influence of yoga gymnastics on cognitive changes in the elderly